Towards a Sociological Understanding of Sexting as a Social Practice: A Case Study of University Undergraduate Men. (April 2020) - Roberts, Steven; Ravn, Signe
This article makes the case for understanding young people's engagement with 'sexting' as a social practice. Moving away from the dominant focus on teenagers and (sexual) risk and instead approaching sexting as an 'everyday' practice sheds light on how sexting is perceived and situated as a normalised part of contemporary youth culture. Drawing on 10 focus groups with 37 undergraduate men in Melbourne, Australia, our data reveal young men's significant emphasis on consent, mutuality and respect, marking out 'appropriate sexting' practices as distinct from harassment or image-based abuse. Nonetheless, the centrality of a transactional approach to sexting questions those seemingly positive dispositions. Social practice theory permits sophisticated understanding of these nuances, seeing them as bound up and produced in correspondence with the broader meanings, embodied skills and material artefacts that are associated with sexting.